PERLINDUNGAN HUKUM KREDITUR PEMEGANG HAK FIDUSIA TERHADAP OBJEK JAMINAN FIDUSIA YANG DISITA PENGADILAN BERKAITAN DENGAN TINDAK PIDANA PENCUCIAN UANG (Studi Putusan MA No. 1607 K/PID.SUS/2012) - MIRZA PRIMA KUSUMANINGAYU (PREMISE LAW JURNAL, 2015)
Consumer financing is a credit agreement between finance company as the creditor and consumers as the debtors on purchasing products by installment by the consumers. The research used judicial normative and descriptive analytic approach. The result of the research showed that fiduciary collateral confiscated by the Court related to the debtor (Malinda Dee) in the banking criminal case and money laundering still became the authority of the holder of fiduciary collateral, based on droit de suite and droit de preference principles stipulated in Law No. 42/1999 on Fiduciary. The Ruling of the Supreme Court finally gave legal protection for PT ASF and Citibank in which the provision stated that the confiscated fiduciary collateral, a Ferrari Scuderia Type F430, was returned to Citibank with the obligation to pay all liabilities related to the fiduciary giver (Malinda Dee) on the fiduciary collateral.   Keywords: Fiduciary Collateral, Confiscation Court, Criminal Act